2020
DOI: 10.25139/jai.v4i1.2221
|View full text |Cite
|
Sign up to set email alerts
|

Pengelolaan Work Values Pada Gen Y Dalam Meningkatkan Komitmen Kerja

Abstract: Salah satu tantangan baru bagi dunia kerja adalah tingginya jumlah millennial (Generasi Y) yang masuk kedalam dunia kerja dengan keistimewaan yang cenderung berbeda dengan generasi-generasi sebelumnya. Dalam dunia pekerjaan, millennial sering disebut-sebut sebagai generasi yang menyukai kebebasan dan fleksibilitas seperti kebebasan belajar, bekerja, maupun berbisnis. Generasi ini juga dikatakan sebagai challenge seeker. Tahun 2020 hingga tahun 2030 diprediksi bahwa Indonesia akan mencapai puncak populasi usia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Work value is an evaluative standard believed to be true or important and related to work or the work environment. Meanwhile, according to Ros, it means that work value is a general belief about the relative desirability of various aspects of work such as salary, working conditions, achievements, and so on (Filatrovi, 2020).…”
Section: Work Valuementioning
confidence: 99%
“…Work value is an evaluative standard believed to be true or important and related to work or the work environment. Meanwhile, according to Ros, it means that work value is a general belief about the relative desirability of various aspects of work such as salary, working conditions, achievements, and so on (Filatrovi, 2020).…”
Section: Work Valuementioning
confidence: 99%
“…There is a study conducted to reconfirm previous instruments and indicators related to employee intention to stay at the organization [30] which is related to organizational loyalty, while another study found out how the loyalty of millennial consumers on mobile banking applications [32] which is strongly related to customer loyalty. In organizational commitment, a study mentioned how work values relationship with organizational commitment [22], and this is the only study that used organizational commitment as a variable.…”
Section: Lack Of Studies In Millennial Generation Organizational Comm...mentioning
confidence: 99%